Crime Stories and Infamous Fictions. Crime in Roberto Arlt’s Latest Journalistic Production - Juárez, Laura (Anales de Literatura Hispanoamericana, 2009)
Crime is characteristic of Roberto Arlt’s literature from the beginning of his work. However, by the late 1930s his modes of representation are reformulated in the journalistic chronicles of “Tiempos Presentes” and “Al margen del cable” which Arlt published in the daily El Mundo between 1937 and 1942. The essay studies a zone from these articles where “juicy stories” centred on delinquency appear, built from the international newswires which arrived to the newspaper; the subject matter to be narrated by the chronicle becomes, therefore, an unexpected and astonishing issue about the crime world which dissociates itself from the localism pertaining to social criticism (present in Arlt’s “Aguafuertes porteñas” translated Etchings from Buenos Aires), and whose temporal linkage is the starting point for the fictional expansion. They are stories about impostors, professional murderers, smugglers, swindlers, traitors, conspirators; case-narrations where the criminal fact, “striking or curious” and, many times, anecdotic and circumstantial gives them a trait of membership to turn them into stories to be told and which, hence, come close to the tales in Historia universal de la infamia by Jorge Luis Borges and other similar works of the time. Simulators, traitors, American and Eastern gangsters, cold blood murderers, the infamous wander through Arlt’s texts, and his chronicles, like in Borges, also international or universal appear, repeatedly, close to biography.